Consent for paediatric and perinatal postmortem investigations: Implications of less invasive autopsy. (March 2016) - Judge-Kronis, L.; Hutchinson, J.C.; Sebire, N.J.; Arthurs, O.J.
Abstract: The majority of perinatal and paediatric deaths do not fall within the jurisdiction of the Coronial medicolegal system; the decision to consent to autopsy is a personal choice, made by parents on behalf of their child in order to better understand the circumstances of their death, to answer specific questions or to improve the process for others. Professionals seeking to obtain informed consent should understand the general autopsy process as well as the complete range of options available, with their advantages and disadvantages for specific clinical scenarios. This article summarises the principles of obtaining consent for perinatal or paediatric autopsy in the UK at the time of publication. Highlights: Investigation after death should be viewed as a continuation of patient care. Staff training and understanding is crucial to optimising parental choice. Understanding less-invasive approaches will help guide parents. We outline the considerations that may be encountered in the consent process. We emphasise the importance of parental choice throughout.